The impact of e-commerce on transportation dependency - Loh, Lina; Koh, Cheu Shan; Ting, Iong Chen; Aziz, Zulkufli (2017)
Growth of world population has directly caused traffic congestion particularly in the cities.With the development of technologies such as the internet applications have changed the way of doing things.The e-commerce allows buying to be done at any place and at any time, in the word, subjected to the availability of internet connections.The e-commerce has impacted the buying behaviour and business operations. Ecommerce is boomed as it provides the virtual platform to trade the goods and services by just a click without brick and mortal store.It has the ability to re-direct consumer to shop from physical store to online marketplace around the globe. The individuals’ journeys to the stores are replaced by frequent deliveries by the courier companies. Growing of e-commerce is able to reduce the private vehicles on road as the delivery services provide by e-retailer.This paper provides more insights into the relationships between e-commerce and transportation dependency.This study examines the role of buying behavior in e-commerce in affecting the transportation dependency in Malaysia. Non probability convenient sampling method used to collect the data from the students studying at Universiti Utara Malaysia (UUM).The data were collected from 400 undergraduate students in UUM by using semi-structured questionnaire.In the pilot test, the Cronbach’s alpha score is 0.927, which is reliable.The findings are expected to widen the knowledge regard the impacts of e-commerce on transportation dependency.